Bilaterally Symmetrical Lower Extremity Compartment Syndrome following Massive Transfusion - Gulsah Karaoren; Nurten Bakan; Senay Goksu Tomruk; Zelin Topaç; Tuhan Kurtulmuş; Saime Irkören (Case Reports in Orthopedics)
Compartment syndrome is a serious condition characterized by raised intracompartmental pressure, which develops following trauma. Well leg compartment syndrome (WLCS) is a term reserved for compartment syndrome in a nontraumatic setting, usually resulting from prolonged lithotomy position during surgery. In literature, 8 cases have been reported regarding well leg compartment syndrome in a supine position and bilateral symmetrical involvement was observed in only 2 cases. In WLCS etiology, lengthy surgery, lengthy hypotension, and extremity malpositioning have been held responsible but one of the factors with a role in the etiology may have been the tissue oedema and impaired microcirculation formed from the effect of vasoactive mediators expressed into the circulation associated with the massive blood transfusion. The case is presented here regarding symmetrical lower extremity compartment syndrome after surgery in which massive transfusion was made for gross haemorrhage from an abdominal injury. In conclusion, blood transfusion applied at the required time is life-saving but potential risks must always be considered.